Food restriction, but not seasonality, modulates the acute phase response of a Neotropical bat - Cabrera-Martinez, Lucia V. [UNESP]; Herrera M, L. Gerardo; Cruz-Neto, Ariovaldo P. [UNESP] (Elsevier B.V., 2019)
Season and food intake are known to affect immune response of vertebrates yet their effects on metabolic rate have been rarely explored. We tested the effect of season and acute food restriction and their interaction on the energetic cost of immune response activation of a tropical vertebrate, the Seba's short-tailed fruit bat (Carollia perspicillata). We specifically stimulated the acute phase response (APR) with bacterial lipopolysaccharide (LPS) to measure metabolic changes along with changes in body temperature (T-b), body mass (M-b), white blood cell counts and the Neutrophil/Lymphocyte ratio (N/L). We found no effect of season on the different factors associated to the activation of the APR. In contrast to our expectations, unfed bats reached similar T-b increments and RMR peak values and had higher RMR scope values and higher caloric costs than fed bats after LPS injection. However, food deprivation led to delayed metabolic response indicated by longer time required to reach peak RMR values in unfed bats. Both food-deprived and fed bats did not present leukocytosis after APR activation and their WBC counts were similar, but unfed bats had a significant increase of N/L. APR activation represented a small fraction of the bat daily energy requirements which might explain why unfed bats were not limited to mount a metabolic response. Our study adds to recent evidence showing that activating the innate immune system is not an energetically expensive process for plant-eating bats.
Keywords: Energetic cost; Immune response; Acute phase response; Metabolic rate; Seasonality; Food restriction